Emotional Intelligence and Employee Performance in Public Health: The Role of Work Experience as a Moderator - Putri, Wulan Cahya; Gunawan, Asep; Febriyansyah, Hevy (Journal of Educational Management Research, 2025)
This study investigates the influence of emotional intelligence on job performance, with work experience as a moderating variable. Employing a quantitative approach with a descriptive-verificative design, data were collected through structured questionnaires distributed to all 62 employees. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0 software. The results reveal that emotional intelligence has a significant and positive effect on job performance. Employees with higher emotional intelligence demonstrate greater interpersonal competence, adaptability, and decision-making effectiveness—attributes that are essential in healthcare service delivery. Moreover, work experience also positively influences job performance, suggesting that practical exposure enhances task proficiency and professional maturity. Importantly, the study confirms a significant moderating effect of work experience in the relationship between emotional intelligence and job performance, indicating that experience strengthens the positive impact of emotional intelligence. These findings underscore the importance of fostering both emotional intelligence and relevant work experience to improve individual and organizational performance, particularly in service-oriented public institutions such as community health centers.